Enhancing biopolymer composite films: Molecular interaction and functional properties of chitosan and chlorella vulgaris blends for sustainable packaging - Nur Nadiah, Che Aziz; Nur Hidayah, Mat Yasin; Fatmawati, Adam; Siti Rahmah, Esa (Springer New York LLC, 2025)
The study investigates the molecular interactions, physico-chemical and mechanical properties of biopolymer blends comprising chitosan (CS) and Chlorella vulgaris biomass (CVB) to explore the interaction between two components at the molecular level and to determine the influence of these interactions on the resulting composite film properties. Time-of-Flight Secondary Ion Mass Spectrometry (ToF–SIMS) analysis showed increased ion intensity, attributed to intermolecular interactions, especially between amine, sulfate, hydroxide, and hydrogen ions. Zeta potential provided insights into the electrokinetic behavior of the chitosan, microalgae and polyethylene in suspension, indicating their stability for aggregation. The morphological changes and functional groups resulted from chitosan-Chlorella vulgaris biomass (CS-CVB) composite film, attributed to an increased density of hydrogen bonds formed between the two components. When the CVB content was increased from 10 to 30%, the tensile strength of composite film increased by 40.66 MPa. The addition of CVB increased the moisture content but decreased the water solubility of composite films. Additionally, the higher content of CVB led to decrease in the water vapor permeability of the composite films. These findings illuminate the molecular mechanisms underlying the formation of the composite film material and application in food packaging. This addresses the demand for sustainable alternatives in the packaging industries while also promoting an eco-friendly environment.